Advances in Cardiotoxicity Induced by Altered Mitochondrial Dynamics and Mitophagy - Yin, Yiyuan; Shen, Haitao (Frontiers in Cardiovascular Medicine, 2021)
Mitochondria are the most abundant organelles in cardiac cells, and are essential to maintain the normal function of the cardiac. The maintenance of normal cardiac function requires mitochondrial dynamics to ensure the stability of mitochondrial quantity and quality. Mitochondrial dynamics includes mitochondrial fission, mitochondrial fusion and mitophagy. Under normal physiological conditions, the three coordinate to maintain the dynamic balance of the internal environment of cardiac cells. However, when mitochondria are affected by continuous injury factors, the dynamics of mitochondria is unbalanced. Aging and damaged mitochondria cannot be completely removed in cardiac cells, resulting in energy supply disorder and accumulation of toxic substances in cardiac cells, resulting in cardiac damage and cardiotoxicity. This paper summarizes the specific underlying mechanisms by which various adverse factors interfere with mitochondrial dynamics to produce cardiotoxicity and emphasizes the crucial role of oxidative stress in mitophagy. This study aims to provide fresh ideas for exploring the changes in mitochondrial dynamics and their association with cardiotoxicity.